Revisiting the Prominent Anti-Tumoral Potential of Pre-mNK Cells - Guimont-Desrochers, Fanny; Lesage, Sylvie (Frontiers in Immunology, 2013)
Interferon-producing killer dendritic cells (IKDC) were first described for their outstanding anti-tumoural properties. The “IKDC” terminology implied the description of a novel DC subset and initiated a debate on their cellular lineage origin. This debate shifted the focus away from their notable anti-tumoural potential. IKDC were recently redefined as precursors to mature NK (mNK) cells and consequently renamed pre-mNK cells. Importantly, a putative human equivalent of pre-mNK cells was recently associated with improved disease outcome in cancer patients. It is thus timely to revisit the functional attributes as well as the therapeutic potential of pre-mNK cells in line with their newly defined NK cell precursor function.